2022
DOI: 10.32604/phyton.2022.021507
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Auxin Transport in the Early Response of the Arabidopsis Root System to Inoculation with Azospirillum brasilense

Abstract: The potential of Plant Growth Promoting Rhizobacteria (PGPR) has been demonstrated in the case of plant inoculation with bacteria of the genus Azospirillum which improves yield. A. brasilense produces a wide variety of molecules, including the natural auxin indole-3-acetic acid (IAA), as well as other phytoregulators. However, several studies have suggested that auxin induces changes in plant development during their interaction with the bacteria. The effects of A. brasilense Sp245 on the development of Arabid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…One study used Helicobacter Azotrophicus inoculation to examine the impacts of root development in Arabidopsis thaliana in Brazil. The findings indicated that the growth hormone encouraged the production of lateral root meristematic tissues [75].…”
Section: Regulating Phytohormone Levelsmentioning
confidence: 97%
“…One study used Helicobacter Azotrophicus inoculation to examine the impacts of root development in Arabidopsis thaliana in Brazil. The findings indicated that the growth hormone encouraged the production of lateral root meristematic tissues [75].…”
Section: Regulating Phytohormone Levelsmentioning
confidence: 97%
“…In addition, PGPBs contribute to the synthesis of secondary metabolites, water absorption, nutrient [phosphorus (P), Zn, and potassium (K)] solubilization, and tolerance to biotic and abiotic stresses ( Hungria et al., 2018 ; Jalal et al., 2021 ; Lopes et al., 2021 ). The inoculants of the genus Azospirillum are being recognized in the biosynthesis of auxin synthesis, nutrient cycling and availability, and biological nitrogen (N) fixation by reducing N 2 into ammonia (NH 3 ) ( Bhat et al., 2019 ; Carrillo-Flores et al., 2022 ; Galindo et al., 2022 ). Bacillus subtilis ( B. subtilis ) has the ability to promote plant growth through P solubilization, increase Zn use efficiency, bioremediation of heavy metals, and controlling phytopathogenic infestation, which in turn leads to increased root–shoot development and productivity ( Lobo et al., 2019 ; dos Santos et al., 2021 ; Jalal et al., 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly relevant when considering auxin-producing PGPR bacteria as they represent an important group of PGPR [ 4 , 15 ]. In this work, we address this issue with the α-proteobacterium Azospirillum baldaniorum (previously brasilense ) Sp245, a model PGPR strain in which the bacterial synthesis of indole-3-acetic acid (IAA) has been extensively studied [ 15 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%